2018
DOI: 10.1177/1460408618777773
|View full text |Cite
|
Sign up to set email alerts
|

Is our current method of cervical spine control doing more harm than good?

Abstract: Introduction: Early cervical spine immobilisation has long been considered the standard of care in the management of trauma patients with suspected spinal cord injury. There has been conflicting evidence regarding its benefits and risks. This article reviews the current literature and whether the continued use of routine cervical spine immobilisation is still appropriate in modern trauma care. Method: A literature search was conducted using the Medline PubMed, Google Scholar and Cochrane Library online databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…However, several studies have pointed out possible side effects of a rigid neck brace, such as difficult airway management [ 12 ], cranial pressure due to drainage obstruction [ 13 ], or lack of patient compliance. Therefore, Phaly et Khan [ 14 ] recommended performing cervical spine immobilization only in patients who are considered particularly high-risk. Uzun et al [ 15 ] showed that headblocks and various harness systems may also effectively reduce range of motion.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have pointed out possible side effects of a rigid neck brace, such as difficult airway management [ 12 ], cranial pressure due to drainage obstruction [ 13 ], or lack of patient compliance. Therefore, Phaly et Khan [ 14 ] recommended performing cervical spine immobilization only in patients who are considered particularly high-risk. Uzun et al [ 15 ] showed that headblocks and various harness systems may also effectively reduce range of motion.…”
Section: Discussionmentioning
confidence: 99%
“…In reality however, a more pragmatic approach is often required, particularly in patients with pre-existing spinal conditions, head injury and those at risk of airway compromise or aspiration. 44…”
Section: Critical Imaging Findingsmentioning
confidence: 99%
“…In reality however, a more pragmatic approach is often required, particularly in patients with pre-existing spinal conditions, head injury and those at risk of airway compromise or aspiration. 44 Awareness of the presence of significant spinal injury is useful at the primary survey as the injury pattern may suggest a constellation of further injuries, for example blunt cervical vascular injury, requiring further assessment with CT angiogram and retroperitoneal injury with thoracolumbar Chance-type fracture following lap-belt injury. 45,46 The presence of a rigid spine for example in a patient with ankylosing spondylitis is also worth noting, since this will be more likely to sustain a hyperextension/flexion injury.…”
Section: Spinementioning
confidence: 99%
“…Pre-hospital spinal immobilisation is one such example of this. Like MILS, there is a lack of evidence supporting its efficacy in preventing secondary spinal cord injury and yet this practice is entrenched in trauma practice despite being associated with adverse effects and iatrogenic injury [21,22]. There is now a slow movement towards change in this regard, with some organisations now recommending more selective approaches to the use of spinal immobilisation, especially in cases of penetrating trauma [23,24].…”
mentioning
confidence: 99%